Increasing Quality and Competitiveness of Witpari Culinary MSMEs Through Modern Production and Digital Marketing - Sri Murwanti; Imam Riefly Aditomo; Siti Zulaekah; Afif Faishal; Fauzan Muhammad Ihsan; Heilin Alber Siva Haryoko (Universitas Muhammadiyah Surakarta, 2026)
Rural culinary MSMEs frequently face structural constraints in production efficiency, packaging standardization, and technological literacy, limiting their competitiveness in tourism-based markets. This community service program aimed to strengthen production capacity and hygienic packaging practices within the Witpari Culinary MSME Community in Kemuning Village, Karanganyar. The intervention provided two spinner oil-draining machines and five heat sealer units, supported by participatory technical training and mentoring approaches aligned with Participatory Action Research (PAR) principles. A participatory action research framework was applied through needs assessment, intervention design, hands-on implementation, and evaluation using pre-test and post-test instruments. Baseline results revealed low mechanized production literacy (mean score 42.5/100). After intervention, the mean score increased to 81.3/100, with 85% of participants demonstrating independent operational competency. The program resulted in reduced oil residue, improved packaging durability, increased product professionalism, and enhanced technological self-efficacy among participants. Findings confirm that small-scale appropriate technology combined with structured mentoring significantly enhances operational literacy, standardization, and competitiveness of rural MSMEs.